Analysis of children's referrals to a specialized hearing rehabilitation center (Research, Society and Development, 2022)
Introduction: Newborn hearing screening allows children with risk factors or who failed the test to be referred for an early audiological diagnosis. However, the literature indicates that there is a significant number of children arriving late at diagnostic services. Objective: To analyze the relationships between reason for scheduling, age and audiological diagnosis in a rehabilitation center. Method: Demographic and audiological data were analyzed and collected from the medical records of 276 children scheduled for audiological diagnosis at the SUS accredited hearing health service in 2018. Results: Most children were boys - 58.3%, the mean age at onset of diagnosis was 19.8 months and 27.2% of subjects did not complete the diagnosis. Most of the children who started the diagnosis were babies who failed NHS (37.31%), followed by suspected hearing impairment (26.08%), complaints related to language delay (23.18%) and risk factors. risk (13.4%). Of the 201 children who completed the diagnosis, 55.72% had some level of hearing loss. The median age of children with some degree and type of hearing loss is lower than the median of children without hearing loss (p=0.0019). There was a statistically significant difference (p value = 0.003) between the ages of children without hearing loss and with hearing loss. Conclusion: The study makes it possible to analyze the flow of children's appointments at the service so that a greater number of children can complete the audiological diagnosis properly and start the necessary intervention as soon as possible.